2021
DOI: 10.1002/eat.23478
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone apps for eating disorders: A systematic review of evidence‐based content and application of user‐adjusted analyses

Abstract: Objective To examine the frequency of evidence‐based treatment elements in popular smartphone apps for eating disorders (EDs), and to characterize the extent to which real‐world users encounter different elements. Method We searched the Apple App Store and Google Play Store for apps offering treatment or support to individuals with EDs. Then, we created a codebook of 47 elements found in evidence‐based treatments for EDs. We examined the presence or absence of each element within each ED app. We also acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…Another plausible explanation is that users generally tend to gravitate toward a small number of highly engaging and well-advertised apps. Our findings are not unique to DBT apps: previous research has found similar distributions of active users in apps for depression and anxiety [35], eating disorders [36], and other health conditions [27]. Thus, the large differences between popular and unpopular apps may not be as surprising as it may appear at first glance.…”
Section: Discussionsupporting
confidence: 41%
“…Another plausible explanation is that users generally tend to gravitate toward a small number of highly engaging and well-advertised apps. Our findings are not unique to DBT apps: previous research has found similar distributions of active users in apps for depression and anxiety [35], eating disorders [36], and other health conditions [27]. Thus, the large differences between popular and unpopular apps may not be as surprising as it may appear at first glance.…”
Section: Discussionsupporting
confidence: 41%
“…Participants also described their preferences for intervention features. While many suggestions like education and self-monitoring are common evidence-based elements of apps for eating disorders [ 19 ], these results offer informative specifications for how such components are preferred to be packaged in a digital intervention for this population. For example, results suggest the importance of supporting people in preparing affordable meals (e.g., that stretch beyond a single meal) and that account for the time and expense of obtaining foods.…”
Section: Discussionmentioning
confidence: 99%
“…Two earlier systematic appraisals of the quality of commercially available eating disorder apps conclud ed that very few of them incorporated components of evidence based treatments, with some even providing potentially harmful information 165,166 . However, four commercially available eating disorder apps (Mental Health Tests, Recovery Road, Rise Up, and Psychiatry Pro-Diagnosis, Info, Treatment, CBT & DBT)each of which are grounded in an evidencebased framework -account for 96% of monthly active users according to a recent review 167 , indicating that those resorting to apps to help manage their eating disorder are likely exposed to credible information.…”
Section: Eating Disordersmentioning
confidence: 99%